Waiting and following: Within-industry herding behavior in annual report disclosure - Shijiao Cao; Jiangqiong Wang (China Journal of Accounting Research, 2021)
Using the unique scheduled disclosure system for annual reports in China's stock market, we examine within-industry herding behavior in annual report timing. The results reveal the waiting and following behavior strategies used in the annual reporting process within industry. Firms that originally schedule an early (late) disclosure date within their industry are more likely to reschedule to a later (earlier) date. Informational pressure is the dominant mechanism underlying herding in annual reporting, and capital market reputation incentives mainly induce the herding of bad news. Further analysis shows that delaying disclosure via the waiting strategy reduces the future occurrence of restatements, whereas bringing forward disclosure does not change the propensity of future restatements. Overall, we enrich the limited empirical studies on sequential mandatory disclosure decisions within industry.
Keywords: 650; Financial disclosure; Annual report; Disclosure timing; Herding behavior; Informational pressure; Scheduled disclosure system